Searching relevant polymorphisms of CYP2B6 in HIV infected patients - Tomaz, R.; Fernandes, A.; Cruz, J. P.; Martins, R.; Morais, J. G.; Ribeiro, A. C. (My University, 2015)
"The CYP2B6 belongs to the family of Cytochrome P450 enzymes that catalyze the metabolism of a wide variety of drugs, including the anti-retroviral EFV. The CYP2B6 gene, that has been mapped in the chromosome 19, is highly polymorphic and some SNP, namely 516G>T and 785A>G, are associated with decreased protein expression. These variants are related to phenotypes that are characterized as EFV poor metabolizers, and consequently to episodes of neurotoxicity."
Poster presented at the From Basic Sciences to Clinical Research - First International Congress of CiiEM. Egas Moniz, Caparica, Portugal, 27- 28 November 2015
Keywords: Polymorphisms; CYP2B6; HIV